Les Inquiétudes du destin dans le monde de Caragiale : pour une poétique de la mise en scène - VISARION, Alexa (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
This paper approaches the work of the great Romanian playwright and prose writer I. L. Caragiale from a personal perspective. The author focuses on the concept of destiny and the ambiguities of this concept in Caragiale’s thought. The ambiguity of destiny, always defined between the comic and the tragic, between the sublime and the grotesque, is investigated here, showing that Caragiale had an extraordinary philosophical openness, which he translated into situations and characters. Some emblematic human figures, situations and lines from Caragiale’s work are briefly analysed and the modernity and prophetic nature of his political thought are also treated. All these aspects were elements that stimulated the author’s practical interest in staging or making films inspired by Caragiale’s work. Caragiale profoundly shaped the author’s conception of the actor’s art and the role of theatre direction: this is the conclusion of the present paper.